A Review of Pore Structure Characterization Methods for Hard Carbon Anode Materials in Sodium⁃Ion Batteries - Yuke SHEN; Zifeng MA; Linsen LI; Huan LI (Shiyou huagong gaodeng xuexiao xuebao, 2025)
Sodium?ion batteries are considered a promising alternative to lithium?ion and lead?acid batteries, offering a balance between performance and cost?effectiveness for applications requiring moderate energy density and low cost. Hard carbon stands out as the most promising anode material for sodium?ion batteries, with the majority of scholars attributing its sodium storage capacity primarily to its porous structure. However, characterization techniques for this porous structure are currently very limited. This hinders in?depth analysis of the hard carbon pore structure and makes it more difficult to design performance enhancement strategies. This review provides an overview of current methods for characterizing the pore structure of hard carbon, including transmission electron microscopy, gas adsorption, X?ray small angle scattering, and helium true density testing. The combined use of these methods helps accurately characterize the pore structure of hard carbon and provides research ideas and technical support for the design of high?performance hard carbon anodes.